COMMUNITY TOURISM MANAGEMENT KHLONG NOISUB - DISTRICT MUEANG DISTRICT SURATTHANI PROVINCE - Tipsuk, Suchada; ., Phrakhruphawanachanthakhun; Saengsophon, Phraathikan Thawatchai; Chupradith, Phrapaladphurivisit; Inthachat, Phrakhrusamuditthaphum (Journal of MCU Nakhondhat, 2021)
This research article has the following objectives. 1) To study tourism management by the community 2) to compare community tourism management 3) to study problems, recommendations, community - based tourism management The samples used in the research were people in Klong Noi Sub - district Muang District Suratthani Province, totaling 363 people using questionnaires as a research tool. There was a confidence factor of 0.90. The statistics used for data analysis were was percentage mean standard deviation and the analysis of variance statistics. 1) The results showed that the majority of the samples were female. Aged between the ages of 36 - 50 years, working in trade and personal business Have a bachelor's degree monthly income of 10,001 - 15,000 baht and have more than 10 years of living in the community. The management of tourism by community in Tambon Khlong Noi overall is at a high level. In descending order: management organization, community learning, and natural resources and culture. 2) The comparative results showed that people with Age / education level / monthly income and length of stay in the community are different / opinions Community - based tourism management There was not statistically significant difference at 0.05 level, while occupation was different. 3) ecommendations were found that the natural resources and cultural aspects. Tourist behavior problems tourism objectives, lack of consciousness and responsibility for resource conservation contribute to the rapid deterioration of tourist sites. The results of this research will be used as a guideline for improving community - based tourism management. This will bring about community management in order to create efficiency to be effective for the community sustainably.